PONCOL SEMARANG STATION PARKING CAPACITY ANALYSIS - Masykuroh, Ifana; Rizani, Mohammad Debby; Yudaningrum, Farida (International Journal of Sustainable Building, Infrastructure and Environment (IJOSBIE), 2023)
Currently, train stations are still busy for train passengers, parking capacity requirements are also being considered. This research is motivated by the problem of parking capacity, where there are several points that cause congestion and the direction of the parking lane is less than optimal at Poncol Semarang Station. In overcoming this problem, it is necessary to analyze parking capacity, evaluate problems and alternatives that can be used to solve existing problems. The method used in this research is a descriptive approach. This means that the data collected is not in the form of numerical data, but rather data originating from interview scripts, field notes, personal documents, researcher notes or memos and other official supporting documents which aim to enable researchers to describe the empirical reality behind the conditions that occur at train stations. Poncol Semarang. This research produces parking capacity at the station where the parking area can accommodate 554 SRP for cars and 241 SRP for motorbikes with the most parking accumulation getting the most results on Sunday, August 20 2023, namely in the morning at 06.00-09.00 WIB. Amounting to 157 motorbikes and 100 cars. Alternatives for handling traffic jams during peak parking hours are: moving the motorbike taxi post, improving the direction of the parking lane and moving entrance 2.Keywords: parking, capacity, alternative, station